Zooplankton of the Okavango Delta and associated basins in Botswana - West, Deirdré Theresa (University of the Free State, 2016)
The Okavango Delta, one of the most iconic wetlands on the planet, is the third largest Ramsar site and in 2014 was listed as the 1000th UNESCO World Heritage Site. It is situated in the centre of the Kalahari Basin of southern Africa, which is a semi-desert and the largest continuous sea of sand on earth. The Okavango Delta, in northern Botswana, receives its waters from the Okavango River which originates as many tributaries in Angola and flows as a single river through Namibia’s Caprivi Strip before entering Botswana where it is met by a series of fault lines. These faults control the shape of the delta and result in its water spreading across the Kalahari Sands, forming the world’s largest alluvial fan. Most years there is little to no outflow from the Okavango Delta, but the system recently experienced consecutive years of record high floods from the catchment area in Angola, resulting in the basins associated with the delta being inundated for the first time in up to four decades. This provided the perfect opportunity to study the zooplankton of the Okavango Delta, from which only a few studies have been conducted, and it has allowed an insight into the zooplankton species diversity of the associated basins. The aims of the present study were to obtain specimens of aquatic micro-invertebrates, correctly identify Rotifera and micro-Crustacea material collected up to species level where possible, create a photographic data base of the organisms and to map the distribution of each species throughout the study area. Water bodies included in the study are the Okavango Panhandle, the Okavango Delta Fan, the Thamalakane River, Lake Ngami, the Boteti River and Lake Xau. A total of 33 rotifer species were identified, including three genera (Asplanchnopus de Guerne, 1888, Synchaeta Ehrenberg, 1832 and Sinantherina Bory de St. Vincent, 1826) and six species, i.e. Asplanchnopus multiceps (Schrank, 1793), Epiphanes senta (Müller, 1773), Synchaeta pectinata Ehrenberg, 1832, Conochilus dossuarius Hudson, 1875, Conochilus unicornis Rousselet, 1892 and Sinantherina sp., which have not been identified from the waterways of northern Botswana before. The cladoceran species diversity, excluding the family Chydoridae which was the most diverse, but lacks taxonomic review, totalled 12 species. Amongst these was the species Macrothrix propinqua Sars, 1909 which has not been recorded from the study area previously. The calanoid copepod Tropodiaptomus schmeili (Kiefer, 1926) was present in the Okavango Delta and its associated basins, except in Lake Xau where no calanoids were collected. Furthermore, a possibly undescribed species of Metadiaptomus Methuen, 1910 was found in the Okavango Panhandle and Lake Ngami. Eight species of the order Cyclopoida were collected from the Okavango Delta and its associated basins, five of which were recorded from the system for the first time. Zooplankton studies were also conducted in the Nata River during low flow and results indicated a total of 14 rotifer, cladoceran and copepod species. Unlike the Okavango System where the calanoid genus Tropodiaptomus thrives, Metadiaptomus transvaalensis Methuen, 1910 was found in the Nata River. Furthermore, this calanoid copepod was infested with the peritrich, Trichodina diaptomi Šrámek-Hušek, 1953, of the order Mobilida. Notes on the possible life-history of this trichodinid are provided. The results from the entire study have laid down the framework for future zooplankton research in the waterways of the semi-arid Botswana, where no baseline data exists for many of the life-sustaining water bodies.

Die Okavangodelta, een van die ikoniese vleilande op die planeet, is die derde grootste Ramsargebied en is sedert 2014 as die 1000ste UNESCO Wêrelderfenisgebied gelys. Dit is in die sentraal Kalahari-kom, in suider-Afrika, geleë, wat ‘n halfwoestyn-area is en ook die grootste sandmassa op aarde is. Die Okavangodelta, in noordelike Botswana, word deur die Okavangorivier gevoed, met die oorsprong uit ‘n aantal bergstrome en sytakke vanuit Angola. Die rivier vloei deur die Kaprivistrook van Namibië, na Botswana waar die water oor die Kalaharisand uitsprei en ‘n delta vorm, as gevolg van ‘n reeks geologiese verskuiwings in die aardkors. Hierdie verskuiwings beheer die vorm van die delta, bepaal die verspreiding van die water oor die Kalaharisand en vorm die wêreld se grootste alluviale delta. Meeste jare was daar geen of baie min uitvloei vanuit die Okavangodelta, maar hierdie stelsel het vir die laaste paar agtereenvolgende jare rekord vloede vanaf die opvangsgebied in Angola ontvang. Dit het veroorsaak dat die efemere riviere en mere wat met die delta geassosieer word, vir die eerste keer in jare opgevul het. Hierdie verskynsel het ‘n gulde geleentheid gebied om die soöplankton-spesiediversiteit van die Okavangodelta en die geassosieerde waterliggame te bestudeer, aangesien daar min inligting hieroor bekend is. Die doel van die studie was om akwatiese mikro-ongewerwelde spesies te versamel, die Rotifera en mikro-Crustacea tot en met spesievlak te identifiseer, waar moontlik, en om ‘n fotografiese databasis asook verspreidingskaarte van die organismes saam te stel. Die waterweë wat deel van die studie gevorm het, sluit die Okavangopypsteel, die Okavangodelta, die Thamalakanerivier, Ngamimeer, die Botetirivier en Xaumeer in. In totaal is 33 Rotifera-spesies geïdentifiseer, waarvan drie genera (Asplanchnopus de Guerne, 1888, Synchaeta Ehrenberg, 1832 en Sinantherina Bory de St. Vincent, 1826) en ses spesies, nl. Asplanchnopus multiceps (Schrank, 1793), Epiphanes senta (Müller, 1773), Synchaeta pectinata Ehrenberg, 1832, Conochilus dossuarius Hudson, 1875, Conochilus unicornis Rousselet, 1892 en Sinantherina sp. vir die eerste keer in die studiegebied versamel is. Die Cladocera-spesiediversiteit, uitsluitend verteenwoordigers van die familie Chydoridae, het uit 12 spesies bestaan. Laasgenoemde sluit die spesie Macrothrix propinqua Sars, 1909 in, wat ook tydens die opnames vir die eerste keer versamel is. Die Calanoida-spesie Tropodiaptomus schmeili (Kiefer, 1926), was in die Okavangodelta en al die verwante waterliggame teenwoordig, uitsluitend Xaumeer. ‘n Moontlike nuwe spesie van die genus Metadiaptomus Methuen, 1910 is in beide die Okavangopypsteel en Ngamimeer versamel. Agt spesies van die orde Cyclopoida was in die Okavangodelta en verwante waterliggame versamel, waarvan vyf vir die eerste keer in hierdie stelsel aangeteken is. Soöplankton studies is ook in die Natarivier, tydens ‘n periode van verlaagde watervlakke, uitgevoer. Die resultate van laasgenoemde studie sluit 14 soöplanktonspesies (verteenwoordigers van Rotifera, Cladocera en Copepoda) in. In teenstelling met die Okavangostelsel, waar verteenwoordigers van Calanoida meestal deur die genus Tropodiaptomus verteenwoordig was, was slegs Metadiaptomus traanvaalensis Methuen, 1910 in die Natarivier versamel. Hierdie spesie was met ‘n verteenwoordiger van die Peritrichia, Trichodina diaptomi Šrámek-Hušek, 1953, orde Mobilida, besmet. Inligting rakende die potensiële lewensstrategie van hierdie spesie word ook verskaf. Die resultate van die hele studie vorm die basis vir toekomstige soöplanktonstudies in die waterweë van die semi-ariede Botswana, waarvoor daar tot op hede vir ‘n groot aantal van hierdie lewensonderhoudende waterliggame, geen grondslagdata en inligting beskikbaar was nie.
Thesis (Ph.D. (Zoology and Entomology))--University of the Free State, 2016
Keywords: Boteti River; Cladocera; Copepoda; Distribution; Lake Ngami; Lake Xau; Nata River; Okavango; Rotifera; Species diversity; Thamalakane River; Okavango River Delta (Botswana); Zooplankton -- Botswana